Combination of black cumin seeds with Curcuma xanthorrhiza extract as an antioxidant and immune-modulator agent in the COVID-19 pandemic era - Akrom Akrom; Titiek Hidayati; Nurcholid Umam; Ginanjar Zuhruf Saputri (International Journal of Public Health Science (IJPHS), 2022)
The COVID-19 pandemic demands changes in using of medicinal plants. Empirically, the medicinal plants of Curcuma xanthorrhiza (CX) and black cumin (BC) have been used massively in the era of the COVID-19 pandemic. Curcuma xanthorrhiza and black cumin (CXBC) preparations have been developed with the main ingredients of BC oil and CX extract. The purpose of the study was to determine the antioxidant and immune-modulatory activities of CXBC preparations active substances (polyphenols, flavonoids, thymoquinone). We conducted experimental laboratory research. The immunomodulatory activity test was carried out on human large lung cancer cell line (HTB-183 cells) by observing the expression of tumor necrosis factor alfa (TNF-α) and interleukine 10 (IL-10). The results showed that the CXBC preparation contained 4% thymoquinone, 25.87 mg/ml polyphenols, and 41.86 mg/dl flavonoids. CXBC preparations contain vitamins (A, C, and E) and minerals (potassium, calcium). The antioxidant activity of the CXBC preparation was included in the strong category with IC50=54.87 ppm. CXBC preparations increased TNF-a expression and decreased IL-10 expression in HTB-183 cells. Based on the study results, it can be concluded that the CXBC preparation contains 4% thymoquinone, 25.87 mg/ml polyphenol, 41.86 mg/dl flavonoid, and a high level of vitamin and minerals. CXBC preparations have potent antioxidant activity, increase TNF-α and decrease IL-10 expression.